To solve the factored quadratic equation \((13x−2)(x−34)=0\), we can set each factor equal to zero:
-
Set the first factor to zero: \[ 13x - 2 = 0 \] Solving for \(x\): \[ 13x = 2 \implies x = \frac{2}{13} \]
-
Set the second factor to zero: \[ x - 34 = 0 \] Solving for \(x\): \[ x = 34 \]
So the solutions are \(x = \frac{2}{13}\) and \(x = 34\).
The solution set is: \[ x = \left{ \frac{2}{13}, 34 \right} \]
Therefore, the correct response is: The solution set is \( x = \left{ \frac{2}{13}, 34 \right} \).